(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to explore the nature of the relationship between excessive social media use and the level of family cohesion within the Libyan context, specifically focusing on the city of Az-Zawiya. The study employed a descriptive-analytical approach, utilizing a questionnaire as the primary tool for data collection. The tool was administered to a random sample of (120) individuals from families residing in the municipality of Az-Zawiya Center. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS), employing Pearson correlation coefficients, One-Way ANOVA, and Cronbach’s Alpha for reliability testing. Key Findings: The results demonstrated high levels of reliability and internal consistency for the study scales. Preliminary findings indicated that the "Time Dimension" of usage is the most prominent aspect of excessive use, with high means recorded for spending more than 4 hours daily on digital platforms. The Kolmogorov-Smirnov test confirmed the normality of data distribution, supporting the statistical validity of the correlation between intensive social media usage and the decline in family cohesion indicators (such as dialogue, shared quality time, and role integration). The study concluded with a set of recommendations aimed at enhancing digital literacy and regulating social media usage to preserve family stability and unity.